Préprofessionnaliser de futurs enseignants ou comment organiser les situations de formation pour étayer une substratification expérientielle - Laurent Dastugue; Sébastien Chaliès (Activités)
This study questions the repercussions of the development of an initial vocational training system for student civil servant trainees in Physical and Sports Education on their ability to use the situated normative experiences lived as dancers in a university center during their teaching activity dance in schools. Finding its theoretical justifications within a research program conducted in cultural anthropology, this study allows more precisely to support the hypothesis of an “experiential substratification” between the experiences lived by the students over the different training and job. By way of discussion, the training circumstances at the origin of this experiential substratification are discussed. Avenues for renewing student training methods are being considered (i) learning ENS as dancers, (ii) learning ENS as a future teacher integrating aspects of ENS practice in dance and (iii) teach these ENS carriers of substratification in a modified work situation.